Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1103/physrevd.99.043011
|View full text |Cite
|
Sign up to set email alerts
|

Axion cooling of neutron stars. II. Beyond hadronic axions

Abstract: We study the axion cooling of neutron stars within the Dine-Fischler-Srednicki-Zhitnitsky (DFSZ) model, which allows for tree level coupling of electrons to the axion and locks the Peccei-Quinn charges of fermions via an angle parameter. This extends our previous study [Phys. Rev. D 93, 065044 (2016)] limited to hadronic models of axions. We explore the two-dimensional space of axion parameters within the DFSZ model by comparing the theoretical cooling models with the surface temperatures of a few stars with m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 63 publications
0
50
0
Order By: Relevance
“…Axions have also been associated with the anomalous stellar cooling problem [13,14], including neutron stars [15][16][17]. This is because axions could be produced in hot astrophysical plasmas and, thus, could take part of the energy transport in stellar objects.…”
Section: Introductionmentioning
confidence: 99%
“…Axions have also been associated with the anomalous stellar cooling problem [13,14], including neutron stars [15][16][17]. This is because axions could be produced in hot astrophysical plasmas and, thus, could take part of the energy transport in stellar objects.…”
Section: Introductionmentioning
confidence: 99%
“…Axions with the properties described here not only would perturb the cooling of white dwarfs but they would also modify in a subtle way the evolution of other kind of stars. An extensive review can be found in Giannotti et al, (2017), while Sedrakian (2019) provides a recent analysis of the cooling by DFSZ axions of the neutron star in Cas A. Here only the two more restrictive tests are presented.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of its (model-dependent) coupling to standard model particles, the axion of course also couples to composite particles such as mesons or baryons. One possible method of estimating constraints on the axion decay constant (or equivalently its mass) rests upon this coupling to baryons, in particular to nucleons, namely through nuclear bremsstrahlung processes in stellar objects [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (see also the overviews [4,33,52,53]). The leading order aN coupling has been derived several times since the early days [23,35,[54][55][56].…”
Section: Jhep08(2021)024mentioning
confidence: 99%